2002
DOI: 10.1046/j.1365-3148.2002.00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of five cell salvage machines in coronary artery surgery

Abstract: We evaluated the effectiveness, ease of use and safety of five machines for blood salvage during coronary artery surgery. All were equally effective in concentrating red cells. We measured haemoglobin, packed cell volume, free haemoglobin, white cells, neutrophil elastase, platelets, thrombin-antithrombin complex (TAT), prothrombin activation peptide F1.2, fibrin degradation product (d-dimers), tissue plasminogen activator (tPA) and heparin in wound blood, in washed cell suspensions and in a unit of bank blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 20 publications
4
30
0
1
Order By: Relevance
“…Washing has been shown to improve the in vitro characteristics of stored RBCs. [4][5][6][7][8][9][10][14][15][16][17] Earlier generations of cells washers were labor intensive and considered "open systems," which limited the shelf life of washed cells to 24 hours. Current microprocessor-driven, closed-system cell-washers can be programmed to provide extensive cell washing and an approved shelf life of 14 days.…”
Section: Introductionmentioning
confidence: 99%
“…Washing has been shown to improve the in vitro characteristics of stored RBCs. [4][5][6][7][8][9][10][14][15][16][17] Earlier generations of cells washers were labor intensive and considered "open systems," which limited the shelf life of washed cells to 24 hours. Current microprocessor-driven, closed-system cell-washers can be programmed to provide extensive cell washing and an approved shelf life of 14 days.…”
Section: Introductionmentioning
confidence: 99%
“…An explanation may be that in this study only salvaged wound blood was used whereas in other studies the residual heartlung machine blood was also processed [5,6]. As in earlier studies we found a high standard deviation of IL-6 values between and in patients [1].…”
Section: Discussionmentioning
confidence: 45%
“…Recently, the quality of this washed and concentrated blood was addressed in several studies [1,5,6]. It was found that processing of shed blood by a cell saver led to normalization of some, but not all, inflammatory markers in the processed blood.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments utilizing a technique for collecting, washing and concentrating blood aspirated from the operative field in a semicontinous system employing a centrifuge were conducted in the 1960s (reviewed by Burman) [88]. In addition to reducing the need for homologous transfusion, blood salvaged and washed retains 2,3-DPG concentrations ( twice the level of banked blood) and has normal oxygen-carrying capabilities.…”
Section: Rbc Transfusion-related Effects On Coagulation Proteinsmentioning
confidence: 99%